Barron's TOEFL iBT : - Sharpe, Pamela J. (Barron's, 2013)
The most up-to-date test prep manual on the market, Barron's TOEFL iBT is available as a book only, but can also be purchased with several additional test preparation tools. The manual presents: A general overview of the TOEFL iBT; Seven model TOEFL iBT tests with explanations or examples for all questions; A review of required academic skills, including note taking, paraphrasing, summarizing, and synthesizing; A review of language skills, including listening, speaking, reading, and writing in English.